3D printing dental resin with long-acting antibacterial property and drug resistance and preparation method of 3D printing dental resin

By combining nano-silver particles with modified acrylate polyurethane and modified acrylate epoxy resin, the problems of insufficient hardness and poor antibacterial effect of dental 3D printing resin materials are solved, and long-term antibacterial and anti-drug resistance are achieved, improving long-term antibacterial and anti-drug resistance The stability and mechanical properties of the material are provided with a more reliable solution for dental restoration.

CN119157759APending Publication Date: 2024-12-20ZHUHAI NATURAL COLOR FORMING IMAGING MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411632482.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing dental 3D printing resin materials have insufficient hardness and poor antibacterial effect, which leads to prone to wear and rupture of restorations, increasing the risk of oral diseases, and the antibacterial effect is short, which easily leads to drug resistance problems.

Method used

Using modified acrylate polyurethane and modified acrylate epoxy resin combined with nanosilver particles, a 3D-printed dental resin with long-acting antibacterial and anti-drug resistance was prepared through chemical synthesis method, and the antibacterial use of nanosilver particles was used. Performance and catechol antioxidant enhance the antibacterial stability and mechanical properties of the resin.

Benefits of technology

It significantly improves the antibacterial effect of the resin, extends the antibacterial effect, enhances the hardness and wear resistance of the material, reduces drug resistance problems, and provides more reliable oral repair and orthodontic treatment solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119157759A_ABST
    Figure CN119157759A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printing dental resin with long-acting antibacterial and drug resistance and a preparation method thereof. The 3D printing dental resin comprises the following components in parts by weight: 25-60 parts of modified acrylate polyurethane, 25-40 parts of modified acrylate epoxy resin, 2-8 parts of a photoinitiator, 50-80 parts of a monomer diluent, 0.5-2 parts of an auxiliary agent and 0.5-3 parts of nano-silver particles. According to the antibacterial light-cured resin composite material capable of being used for 3D printing, the nano-silver particles are innovatively added, and the nano-silver particles have excellent biocompatibility and antibacterial characteristics, are safe and harmless to a human body, can effectively inhibit growth of bacteria in an oral cavity, and can be used for preparing the antibacterial light-cured resin composite material, so that the antibacterial light-cured resin composite material can be used for 3D printing. The nano-silver particles can also improve the mechanical properties of the resin material, such as hardness and wear resistance, so that the repaired teeth are more stable and durable, and in addition, the nano-silver particles and the catechol modified acrylate polyurethane can achieve a synergistic effect, so that the antibacterial efficiency is improved, and the service life of the teeth is prolonged. The problem of drug resistance caused by using a single antibacterial agent is also reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of 3D printing, and in particular to a 3D printing dental resin having both long-lasting antibacterial and anti-drug resistance properties. Background Art

[0002] Since its advent, 3D printing technology has been rapidly and widely used in various industries for its characteristics of precision, high efficiency, and strong customization capabilities. This technology manufactures physical objects by stacking materials layer by layer, which not only solves many problems in traditional manufacturing methods, but also brings revolutionary changes to the field of dental medicine. In the field of dentistry, 3D printing resin materials are widely used in the production of braces, braces, and filling materials due to their good biocompatibility, plasticity, and high precision. Compared with traditional plaster models, 3D printed resin models have higher precision and durability, and can more accurately reflect the patient's oral condition. Braces and braces constructed based on 3D printed models can better match patients, providing doctors with more reliable treatment basis and better repair effects.

[0003] However, the currently widely used dental resin materials generally face the challenges of insufficient hardness and poor bactericidal effect. Existing antibacterial dental materials, such as domestic invention patents CN118415887A and 109453034B, can inhibit bacterial reproduction to a certain extent, but the maintenance time is short, and the antibacterial effect and drug resistance are poor. In addition, the lack of hardness may cause the resin material to be easily worn or broken during chewing, thereby shortening the service life of the restoration. Poor antibacterial ability may lead to uncontrolled bacterial growth in the oral cavity, increase the risk of oral diseases such as caries, gingivitis, and periodontitis, and further affect the patient's oral health. In severe cases, it may even endanger the overall health, such as increasing the risk of cardiovascular disease, respiratory diseases, etc. Therefore, it is urgent to improve dental resin materials to enhance their hardness and bactericidal properties to ensure the success of tooth restoration and patient satisfaction. Summary of the invention

[0004] The purpose of the present invention is to provide a 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties and a preparation method thereof to solve the above problems.

[0005] According to one aspect of the present invention, a 3D printing dental resin with long-term antibacterial and anti-drug resistance is provided, which comprises the following components in parts by weight: 25-60 parts of modified acrylate polyurethane, 25-40 parts of modified acrylate epoxy resin, 2-8 parts of photoinitiator, 50-80 parts of monomer diluent, 0.5-2 parts of auxiliary agent and 0.5-3 parts of nano-silver particles; the modified acrylate polyurethane is obtained by hydroxyl addition end-capping of diisocyanate with polyether polyol, catechol series and hydroxyl-containing acrylate under the action of catalyst I; the modified acrylate epoxy resin is obtained by addition of epoxy resin and acrylic acid; the nano-silver particles are obtained by chemical reduction in the presence of silver nitrate, polyvinyl pyrrolidone and ethylene glycol.

[0006] In some embodiments, the preparation method of the modified acrylate polyurethane is as follows: S1. Heat the polyether polyol to 110° C. and, while ensuring that the container is sealed, pump the negative pressure to 0.2 MPa and maintain for 1 hour; S2, the system temperature is lowered to 40-50°C, the catalyst I and the diisocyanate are slowly added dropwise, the temperature is heated to 50-70°C, and the temperature is maintained for reaction for 3-10 hours until the residual -NCO in the product reaches the theoretical -NCO, thereby obtaining a polyurethane intermediate I; S3, after adding the catalyst I dropwise into the polyurethane intermediate I, add the catechol series, control the temperature at 80-100°C, react for 2-10 hours, add the acrylate end-capping agent, continue the reaction until the residual -NCO of the product is less than 5‰, and then stop the reaction to obtain the modified acrylate polyurethane.

[0007] In some embodiments, the polyether polyol includes polypropylene glycol (PPG) and polyethylene glycol (PEG), and the polyether polyol includes at least one of PPG200, PPG400, PPG600, PPG1000, PPG1500, PPG2000, PPG3000, PEG200, PEG300, PEG400, PEG600, PEG1000, PEG2000, and PEG4000; the diisocyanate includes toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, At least one of dicyclohexylmethane diisocyanate and hexamethylene diisocyanate; the catechol series includes at least one of 4-(2-ethylamino)benzene-1,2-diphenol, 4-(2-aminoethyl)-1,2-benzene hydrochloride, 3,4-dihydroxybenzylamine hydrobromide, 3,4-dihydroxynorephedrine, and [2-(3,4-dihydroxyphenyl)-2-hydroxy-ethyl]ammonium chloride; the acrylate end-capping agent includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and pentaerythritol triacrylate.

[0008] In some embodiments, the preparation method of the modified acrylate epoxy resin is as follows: the epoxy resin and the polymerization inhibitor are mixed and heated to 60-120°C, after adding catalyst II, the acrylic acid is slowly added dropwise, and the reaction is heated to 100-160°C. The product epoxy ester is measured to be less than 1 mol / kg and the acid value is less than 2 mg KOH / g, thereby obtaining the modified acrylate epoxy resin.

[0009] In some embodiments, the epoxy resin is an o-cresol type novolac epoxy series resin compound; the inhibitor includes at least one of 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tris(2-methylpropionyloxy)-1,3,5-triazine, p-hydroxyanisole, hydroquinone, and 2,5-dimethylhydroquinone; and the acrylic acid includes at least one of acrylic acid and methacrylic acid.

[0010] In some embodiments, the preparation method of the nanosilver particles is as follows: A1, dispersing the polyvinyl pyrrolidone into the ethylene glycol solution, mixing evenly at room temperature, then adding the silver nitrate thereto in a dark condition, stirring at room temperature for 30 to 60 minutes until all the solids are completely dissolved; A2, heating the A1 solution to 60-100°C, keeping the temperature for 12-18 hours, taking out the solution and centrifuging it, washing it with ethanol solution, and centrifuging it for more than 3 times; drying the solid product obtained by centrifugation in a forced air drying oven for 12 hours to obtain the nano silver particles.

[0011] In some embodiments, the polyvinyl pyrrolidone includes at least one of polyvinyl pyrrolidone, polyvinyl pyrrolidone, and polyvinyl pyrrolidone.

[0012] In some embodiments, the monomer diluent includes cyclotrimethylolpropane formal acrylate, o-phenylphenoxyethyl acrylate, o-phenylphenoxyethyl acrylate, 4-tert-butylcyclohexyl acrylate, benzyl acrylate, isodecyl acrylate, (ethoxy)phenol acrylate, tetrahydrocannabinol acrylate, ethoxyethoxyethyl acrylate, 1,6-hexanediol diacrylate, (ethoxylated) 1,6-hexanediol diacrylate, hydroxypivalic acid polyglycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, triethylene glycol diacrylate, (ethoxy)bisphenol A diacrylate. At least one of acrylate, tricyclodecane dimethanol diacrylate, polyethylene glycol (400) diacrylate, polyethylene glycol (600) diacrylate, polypropylene glycol (400) diacrylate, trimethylolpropane triacrylate, 3 (ethoxy) trimethylolpropane triacrylate, 6 (ethoxy) trimethylolpropane triacrylate, (propoxy) propylene triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, 3 (propoxy) trimethylolpropane triacrylate, ethoxylated pentaerythritol tetraacrylate, (trimethylolpropane) tetraacrylate, and dipentaerythritol pentaacrylate.

[0013] In some embodiments, the photoinitiator includes at least one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1-hydroxycyclohexylphenyl ketone, and 2-isopropylthioxanthone; and the auxiliary agent includes at least one of a leveling agent, a defoaming agent, or a wetting and dispersing agent.

[0014] A method for preparing a 3D printing dental resin with both long-lasting antibacterial and anti-drug resistance properties, comprising the following preparation method: at room temperature, adding the modified acrylate polyurethane and the modified acrylate epoxy resin to the monomer diluent and mixing them evenly, adding the auxiliary agent, the photoinitiator and the nanosilver particles, and continuing to mix and stir for more than 30 minutes to obtain the 3D printing dental resin.

[0015] Compared with the prior art, the beneficial effects of this application are: The present invention uses acrylate polyurethane modified by catechol series with excellent antibacterial effect and nano silver particles. The polyphenol structure has strong antioxidant properties, can remove active oxygen free radicals in bacteria, interfere with the redox balance of bacteria, affect its normal metabolism and promote the generation of active oxygen, and this active oxygen has a bactericidal effect. At the same time, catechol can also simulate the behavior of natural antimicrobial peptides, by destroying bacterial cell membranes and inhibiting microbial growth, enhancing the killing effect of other drugs on bacteria. In addition, nano silver particles themselves have strong antibacterial properties, they can penetrate the cell wall of bacteria and interfere with its metabolic process, causing bacterial death. When these two substances are combined, the acrylate polyurethane modified by catechol can be ion-complexed with the enhanced nano silver particles, further enhancing its stable sustained release and lasting antibacterial dispersibility in the resin system, and improving the biological activity of the material surface, so that the antibacterial effect of the entire composite system is significantly improved. The synergistic effect of the two antibacterial materials not only improves the antibacterial efficacy of the resin, but also reduces the drug resistance problem caused by the use of a single antibacterial agent. This innovation is designed to overcome the challenges faced by traditional dental resin materials, including insufficient antibacterial properties, low hardness and slow curing rates.

[0016] The antibacterial photocurable resin composite material for 3D printing provided by the present invention comprises a modified acrylate polyurethane polymer and a modified acrylic acid grafted epoxy resin oligomer. The modified acrylate polyurethane has a higher degree of polymerization, and compared with traditional resins, the curing shrinkage rate is greatly reduced, ensuring the accuracy and stability of the printed parts. In addition, the catechol analogue with disinfection function is innovatively grafted into the molecular side chain of the acrylate polyurethane, rather than simply physically mixing, to increase the structural stability of the material and stabilize the antibacterial activity.

[0017] The mechanical properties of epoxy resin oligomers modified with acrylic acid have been greatly improved, providing higher strength and excellent wear resistance for dental resins, and providing more reliable and durable solutions for oral restorations, orthodontic treatments and other fields.

[0018] The present invention provides an antibacterial photocurable resin composite material that can be used for 3D printing, which innovatively adds nanosilver particles. Nanosilver particles have excellent biocompatibility and antibacterial properties, which are safe and harmless to the human body and can effectively inhibit the growth of bacteria in the oral cavity. In addition, nanosilver particles can also improve the mechanical properties of resin materials, such as increasing hardness and wear resistance, so that the repaired teeth are more stable and durable. In addition, nanosilver particles and catechol-modified acrylate polyurethane can work synergistically, which not only improves the antibacterial efficiency, but also reduces the drug resistance problem caused by the use of a single antibacterial agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1This is the nuclear magnetic hydrogen spectrum characterization diagram of active polyphenol modified acrylate polyurethane; Figure 2 Characterization diagram of the antibacterial properties of the control group and different modified experimental groups. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the following examples, the o-cresol novolac epoxy resin used was produced by Nan Ya Plastics Industrial Co., Ltd., and its epoxy equivalent weight was 200-215 g / eq. Unless otherwise specified, all other reagents were commercially available chemically pure standard products. The operations mentioned in the experimental process are all basic technical means familiar to those skilled in the art.

[0022] Example 1 Add 20 parts of polyethylene glycol 800 and 50 parts of polypropylene glycol 2000 to a container equipped with a temperature measuring device and a stirring device, slowly heat to 110°C, and under the condition of ensuring that the container is sealed, pump the negative pressure to 0.2MPa and maintain for 1 hour. Cool the system to 50°C, add 0.05 parts of diethyltin dilaurate, and then slowly drop 17 parts of hexamethylene diisocyanate, heat to 70°C, and maintain the temperature to react until the residual -NCO in the product reaches the theoretical value to obtain polyurethane intermediate I.

[0023] The polyurethane intermediate I was heated to 50°C, 0.05 parts of diethyltin dilaurate and 3.5 parts of 4-(2-aminoethyl)-1,2-benzenediol hydrochloride were added, the temperature was controlled at 80°C, and the reaction was carried out for 3 hours. Subsequently, 10 parts of hydroxyethyl methacrylate were added, and the reaction was continued until the residual -NCO of the measured product was less than 5‰, and the reaction was stopped to obtain the target acrylate polyurethane.

[0024] Add 74 parts of epoxy resin and 0.3 parts of hydroquinone to a container equipped with a temperature measuring device and a stirring device, stir evenly and heat to 90°C, add 0.1 parts of triphenylphosphine, slowly drop 26 parts of acrylic acid, and heat to 120°C until the product epoxy ester is less than 1 mol / kg and the acid value is less than 2 mg KOH / g, thus obtaining the target acrylate epoxy resin.

[0025] Disperse 1.34 parts of polyvinyl pyrrolidone (K90) into 97 parts of ethylene glycol solution and mix evenly at room temperature. Then, add 1 part of silver nitrate to it under light-proof conditions and stir at room temperature for 30-60 minutes until all solids are completely dissolved. Heat the above solution to 80°C and keep it warm for 13 hours. Take out the solution and centrifuge it, wash it with ethanol solution, and centrifuge it more than 3 times. Dry the solid product obtained by centrifugation in a forced air drying oven for 12 hours to obtain the target nanosilver particles.

[0026] After 50 parts of acrylate polyurethane, 50 parts of acrylate epoxy resin, and 100 parts of polyethylene glycol (400) diacrylate were stirred uniformly at room temperature, 4 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, 0.5 parts of wetting dispersant BYK333, and 1 part of nano silver particles were added, and the mixing and stirring was continued for more than 30 minutes to obtain a composite resin 1.

[0027] Example 2 Add 58 parts of polyethylene glycol 1000 to a container equipped with a temperature measuring device and a stirring device, slowly heat it to 110°C, and while ensuring that the container is sealed, pump the negative pressure to 0.2MPa and maintain it for 1 hour. Cool the system to 45°C, add 0.05 parts of dibutyltin diacetate, and then slowly drop 25.5 parts of isophorone diisocyanate, heat to 75°C, and maintain the temperature to react until the residual -NCO in the product reaches the theoretical value to obtain polyurethane intermediate I.

[0028] The polyurethane intermediate I was heated to 60°C, 0.5 parts of dibutyltin diacetate and 3.5 parts of 4-(2-ethylamino)benzene-1,2-diphenol were added, the temperature was controlled at 85°C, and the reaction was carried out for 4 hours. Subsequently, 13 parts of hydroxypropyl methacrylate were added, and the reaction was continued until the residual -NCO of the measured product was less than 5‰, and the reaction was stopped to obtain the target acrylate polyurethane.

[0029] Add 74 parts of epoxy resin and 0.3 parts of p-hydroxyanisole to a container equipped with a temperature measuring device and a stirring device, stir evenly, heat to 90°C, add 0.1 parts of tetrabutylammonium bromide, slowly drop 31 parts of methacrylic acid, and heat to 110°C until the product epoxy ester is less than 1 mol / kg and the acid value is less than 2 mg KOH / g, thus obtaining the target acrylate epoxy resin.

[0030] Disperse 1 part of polyvinyl pyrrolidone (K30) into 95 parts of ethylene glycol solution and mix evenly at room temperature. Then, add 1 part of silver nitrate to it under light-proof conditions and stir at room temperature for 30-60 minutes until all solids are completely dissolved. Heat the above solution to 80°C and keep it warm for 15 hours. Take out the solution and centrifuge it, wash it with ethanol solution, and centrifuge it more than 3 times. Dry the solid product obtained by centrifugation in a forced air drying oven for 12 hours to obtain the target nanosilver particles.

[0031] After 60 parts of acrylate polyurethane, 40 parts of acrylate epoxy resin, 50 parts of polyethylene glycol (400) diacrylate, and 50 parts of polypropylene glycol (400) diacrylate were stirred uniformly at room temperature, 4 parts of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts of wetting dispersant BYK163, and 1 part of nano silver particles were added, and the mixing and stirring was continued for more than 30 minutes to obtain composite resin 2.

[0032] Example 3 Add 65 parts of polypropylene glycol 2000 to a container equipped with a temperature measuring device and a stirring device, slowly heat it to 110°C, and under the condition of ensuring that the container is sealed, pump the negative pressure to 0.2MPa and maintain it for 1 hour. Cool the system to 55°C, add 0.05 parts of dibutyltin octoate, and then slowly drop 17 parts of dicyclohexylmethane diisocyanate, heat to 70°C, and maintain the temperature to react until the residual -NCO in the product reaches the theoretical value to obtain polyurethane intermediate I.

[0033] The polyurethane intermediate I was heated to 60°C, 0.5 parts of dibutyltin octoate and 3 parts of 3,4-dihydroxybenzylamine hydrobromic acid were added, the temperature was controlled at 85°C, and the reaction was carried out for 3 hours. Subsequently, 15 parts of pentaerythritol triacrylate were added, and the reaction was continued until the residual -NCO of the measured product was less than 5‰, and the reaction was stopped to obtain the target acrylate polyurethane.

[0034] Add 74 parts of epoxy resin and 0.3 parts of 2,6-di-tert-butyl-4-methylphenol to a container equipped with a temperature measuring device and a stirring device, stir evenly and heat to 90°C, add 0.1 parts of trioctylmethylammonium chloride, slowly drop 26 parts of acrylic acid, and heat to 120°C until the product epoxy ester is less than 1 mol / kg and the acid value is less than 2 mg KOH / g, and the target acrylate epoxy resin is obtained.

[0035] Disperse 1.5 parts of polyvinyl pyrrolidone (K120) into 95 parts of ethylene glycol solution and mix evenly at room temperature. Then, add 1 part of silver nitrate to it under light-proof conditions and stir at room temperature for 30-60 minutes until all solids are completely dissolved. Heat the above solution to 80°C and keep it warm for 18 hours. Take out the solution and centrifuge it, wash it with ethanol solution, and centrifuge it more than 3 times. Dry the solid product obtained by centrifugation in a forced air drying oven for 12 hours to obtain the target nanosilver particles.

[0036] After 40 parts of acrylate polyurethane, 60 parts of acrylate epoxy resin, 50 parts of polyethylene glycol (600) diacrylate, and 50 parts of polypropylene glycol (400) diacrylate were stirred uniformly at room temperature, 4 parts of 2-isopropylthioxanthone, 0.5 parts of wetting dispersant BYK333, and 1 part of nanosilver particles were added, and the mixing and stirring was continued for more than 30 minutes to obtain composite resin 3.

[0037] Comparative Example 1 Composite resin 4 is different from Example 1 in that 4-(2-aminoethyl)-1,2-benzenediol hydrochloride is not added during the synthesis of acrylate polyurethane, and the amount of hydroxyethyl methacrylate added is changed to 14 parts.

[0038] Comparative Example 2 Composite resin 5 is different from Example 1 in that polyethylene glycol 800 and polypropylene glycol 2000 are not added during the synthesis of acrylate polyurethane, and the added hydroxyethyl methacrylate is changed to 25 parts.

[0039] Comparative Example 3 Composite resin 6 is different from Example 1 in that modified acrylate polyurethane is not added to the composite resin, and the acrylate epoxy resin is changed to 100 parts.

[0040] Comparative Example 4 Composite resin 7 is different from Example 1 in that no acrylate epoxy resin is added to the composite resin, and the modified acrylate polyurethane is replaced by 100 parts.

[0041] Comparative Example 5 Composite resin 8 is different from Example 1 in that nanosilver particles are not added to the composite resin.

[0042] Comparative Example 6 Composite resin 9 is different from Example 1 in that the amount of 4-(2-aminoethyl)-1,2-benzenediol hydrochloride is changed to 1.5 parts during the synthesis of acrylate polyurethane.

[0043] Comparative Example 7 Composite resin 10 is different from Example 1 in that the amount of 4-(2-aminoethyl)-1,2-benzenediol hydrochloride is changed to 2.5 parts during the synthesis of acrylate polyurethane.

[0044] Comparative Example 8 Composite resin 11 is different from Example 1 in that the amount of 4-(2-aminoethyl)-1,2-benzenediol hydrochloride is changed to 4.5 parts during the synthesis of acrylate polyurethane.

[0045] Comparative Example 9 The difference between the composite resin 12 and the embodiment 1 is that 0.5 parts of nano silver particles are added into the composite resin.

[0046] Comparative Example 10 The difference between the composite resin 13 and the embodiment 1 is that 1.5 parts of nano silver particles are added into the composite resin.

[0047] Combination Figure 1, NMR hydrogen spectrum characterization diagram of active polyphenol modified acrylate polyurethane, deuterated D6-DMSO was used as the test reagent for hydrogen spectrum characterization of the sample, and the multiple peaks with chemical shifts near 6.7~7.0 correspond to the molecular vibration peaks of the phenolic hydroxyl group of the active polyphenol, indicating that the active polyphenol was successfully grafted into the molecular chain of the polyurethane; the strong peak near 2.9~3.3 corresponds to the carbon-hydrogen molecular vibration peak of the propylene double bond, which fully indicates that the end-capping reaction of the propylene double bond was successfully carried out to obtain the target polyphenol modified acrylate polyurethane type photosensitive resin.

[0048] Through DLP (digital light processing) technology, the antibacterial dental resin material is precisely printed and formed, and then post-cured in a UV curing box with a wavelength range of 385~405nm, finally producing a milky white temporary crown with uniform color.

[0049] Curing shrinkage test: Strictly following the standard test process of GB / T 15223-2008, the shrinkage of the composite resin materials in the embodiments and comparative examples after printing and light curing was tested. The test results are shown in Table 1.

[0050] Table 1: Curing shrinkage test of comparative examples and experimental examples According to the data in Table 1, the shrinkage of the composite materials without modified acrylate polyurethane or polyether polyol in the resin is higher than 5%. In contrast, the shrinkage of the composite resin with acrylate polyurethane added is significantly reduced to between 1.5% and 2%. This is because polyether polyol has a large molecular weight and a relatively flexible chain segment, which can form a relatively relaxed network structure during the polymerization process. This structure effectively reduces the internal stress between molecules, thereby reducing the shrinkage of the material during the curing process. In addition, polyether polyol is rich in ether bonds (-O-), which not only give the material better flexibility, but also provide a higher degree of rotational freedom, which helps to form a more stretched polymer chain structure, further alleviating the shrinkage phenomenon during curing.

[0051] Mechanical properties test: In order to further evaluate the physical properties of the antibacterial dental resin materials in Examples 1-3 and Comparative Examples 1-5, we used LCD printers (panel photocuring), DLP printers (projection photocuring) or SLA (stereoscopic photocuring) printers to print these materials into standard test specimens. Subsequently, we strictly followed international standards such as ASTMD638 (tensile strength and modulus test), ASTM D790 (bending performance test), ASTM D256 (impact strength test) and ASTM D2240 (rubber hardness test) to conduct comprehensive mechanical property tests on the prepared specimens. The test results are detailed in Table 2, which clearly shows the performance of each specimen under different test items.

[0052] Table 2: Mechanical properties test of comparative examples and experimental examples According to the data in Table 2, the composite resin material with acrylate epoxy resin exhibits excellent mechanical properties. This is mainly due to the high cross-linking density and stable three-dimensional network structure formed by acrylate epoxy resin during the curing process, and the distribution of acrylate and epoxy groups on the molecular chain improves the cohesion and tensile strength of the material. In addition, good intermolecular compatibility effectively reduces internal stress and achieves a balance between toughness and rigidity. Combined with the thermal stability and chemical corrosion resistance of the epoxy resin itself, the stability and durability of the material under various environmental conditions are ensured.

[0053] Antibacterial performance test: In order to further determine the amount of catechol analogs and nanosilver particles added, the standard process of GB / T 31402-2023 was strictly followed, and the antibacterial efficacy of Example 1 and Comparative Examples 6-10 against Escherichia coli (ATCC8739) was evaluated. The number of viable colonies of each resin sample was tested 1 day, 3 days, 5 days, and 7 days after inoculation with Escherichia coli, and the test results are summarized in Table 3 below. Among them, the average number of viable bacteria measured immediately after inoculation of the sample without antibacterial treatment was 1.2×104cfu / cm2, and the average number of viable bacteria after inoculation for 3, 5, and 7 days is shown in Table 3 below.

[0054] Table 3 Antibacterial performance test of comparative examples and experimental examples - Escherichia coli (ATCC 8739) It can be seen from Table 3 that when the amount of catechol series substances added is 3.5% of the total weight of modified acrylic ester polyurethane and the amount of nanosilver particles added is 0.5% of the total weight of the composite resin, the antibacterial effect reaches the best. Further increasing the content of these two components will not continue to improve the antibacterial properties of the composite resin material.

[0055] In order to more intuitively observe and evaluate the effects of different sterilization components on the sterilization effect of composite resins, Figure 2 The colony images of the following samples after adding Escherichia coli and culturing for 7 days are shown: (A) blank control group, (B) composite resin 4 (without catechol series compounds), (C) composite resin 8 (without silver nanoparticles), and (D) composite resin 1 (with catechol series compounds and silver nanoparticles).

[0056] Antibacterial persistence test: The antibacterial performance test was carried out on the prepared resin samples, strictly adhering to the standard process of GB / T31402-2023, focusing on evaluating the antibacterial efficacy of the samples against Escherichia coli (ATCC 8739) and Staphylococcus aureus (ATCC6538P) and the persistence of their antibacterial effects. After the test samples were prepared, they were soaked in physiological saline for several days to simulate the actual environment of dental resin in the oral cavity. Specifically, the 30-day antibacterial rate refers to the data obtained through the antibacterial test after the resin products were soaked in physiological saline for 30 days. The test results are summarized in Tables 4 and 5.

[0057] Table 4: Antibacterial persistence test of comparative examples and experimental examples - Escherichia coli (ATCC 8739) Table 5: Antibacterial persistence test of comparative examples and experimental examples - Staphylococcus aureus (ATCC 6538) According to the data in Tables 4 and 5, it can be concluded that the synergistic effect of catechol-modified acrylate polyurethane and nano-silver particles can effectively play an antibacterial effect. This is mainly because the catechol structure has strong antioxidant properties, which can remove active oxygen free radicals in bacteria, interfere with the redox balance of bacteria, affect their normal metabolism and have a bactericidal effect. At the same time, catechol can also simulate the behavior of natural antimicrobial peptides and inhibit microbial growth by destroying bacterial cell membranes. Nano-silver particles themselves have strong antibacterial properties. They can penetrate the cell walls of bacteria and interfere with their metabolic processes, leading to bacterial death. When these two substances are combined, catechol-modified acrylate polyurethane can undergo ion complexation with nano-silver particles, further enhancing its stable sustained release and lasting antibacterial properties in the resin system, while improving the biological activity of the material surface, so that the antibacterial effect of the entire composite system is significantly improved. At the same time, polyphenols can inhibit the formation of bacterial biofilms, which is an important factor in bacterial drug resistance. Polyphenols enhance the killing effect of other drugs on bacteria by inhibiting the formation of biofilms. This synergistic effect not only improves the antimicrobial efficiency but also reduces the problem of drug resistance caused by the use of a single antimicrobial agent.

[0058] In addition, the presence of acrylate polyurethane and acrylate epoxy resin can significantly extend the sterilization time of the material. This is because both polymers have excellent film-forming properties and stability, and can form a solid protective film on the surface of the material, which helps to slowly release the sterilizing ingredients. At the same time, their excellent adhesion and chemical resistance can significantly enhance the overall stability of the material and ensure that the sterilizing ingredients maintain their activity for a long period of time. The synergistic effect of the two acrylic resins ensures that the sterilizing ingredients are not easily worn or decomposed, thereby effectively extending the sterilization time of the material.

[0059] The present invention uses acrylate polyurethane modified by catechol series with excellent antibacterial effect and nano silver particles. The polyphenol structure has strong antioxidant properties, can remove active oxygen free radicals in bacteria, interfere with the redox balance of bacteria, affect its normal metabolism and promote the generation of active oxygen, and this active oxygen has a bactericidal effect. At the same time, catechol can also simulate the behavior of natural antimicrobial peptides, by destroying bacterial cell membranes and inhibiting microbial growth, enhancing the killing effect of other drugs on bacteria. In addition, nano silver particles themselves have strong antibacterial properties, they can penetrate the cell wall of bacteria and interfere with its metabolic process, causing bacterial death. When these two substances are combined, the acrylate polyurethane modified by catechol can be ion-complexed with the enhanced nano silver particles, further enhancing its stable sustained release and lasting antibacterial dispersibility in the resin system, and improving the biological activity of the material surface, so that the antibacterial effect of the entire composite system is significantly improved. The synergistic effect of the two antibacterial materials not only improves the antibacterial efficacy of the resin, but also reduces the drug resistance problem caused by the use of a single antibacterial agent. This innovation is designed to overcome the challenges faced by traditional dental resin materials, including insufficient antibacterial properties, low hardness and slow curing rates.

[0060] The antibacterial photocurable resin composite material for 3D printing provided by the present invention comprises a modified acrylate polyurethane polymer and a modified acrylic acid grafted epoxy resin oligomer. The modified acrylate polyurethane has a higher degree of polymerization, and compared with traditional resins, the curing shrinkage rate is greatly reduced, ensuring the accuracy and stability of the printed parts. In addition, the catechol analogue with disinfection function is innovatively grafted into the molecular side chain of the acrylate polyurethane, rather than simply physically mixing, to increase the structural stability of the material and stabilize the antibacterial activity.

[0061] The mechanical properties of epoxy resin oligomers modified with acrylic acid have been greatly improved, providing higher strength and excellent wear resistance for dental resins, and providing more reliable and durable solutions for oral restorations, orthodontic treatments and other fields.

[0062] The present invention provides an antibacterial photocurable resin composite material that can be used for 3D printing, which innovatively adds nanosilver particles. Nanosilver particles have excellent biocompatibility and antibacterial properties, which are safe and harmless to the human body and can effectively inhibit the growth of bacteria in the oral cavity. In addition, nanosilver particles can also improve the mechanical properties of resin materials, such as increasing hardness and wear resistance, so that the repaired teeth are more stable and durable. In addition, nanosilver particles and catechol-modified acrylate polyurethane can work synergistically, which not only improves the antibacterial efficiency, but also reduces the drug resistance problem caused by the use of a single antibacterial agent.

[0063] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A 3D printed dental resin with long-lasting antibacterial and anti-resistance properties. It is characterized in that The composition comprises the following components by weight: 25-60 parts of modified acrylate polyurethane, 25-40 parts of modified acrylate epoxy resin, 2-8 parts of photoinitiator, 50-80 parts of monomer diluent, 0.5-2 parts of auxiliary agent and 0.5-3 parts of nano silver particles; The modified acrylic polyurethane is obtained by reacting diisocyanate with polyether polyol, catechol series, and hydroxyl-containing acrylic acid ester under the action of catalyst I to undergo hydroxyl addition termination. The modified acrylate epoxy resin is obtained by addition reaction of epoxy resin and acrylic acid; The nano silver particles are obtained by chemical reduction in the presence of silver nitrate, polyvinyl pyrrolidone and ethylene glycol.

2. The 3D printing dental resin with both long-lasting antibacterial and anti-drug resistance according to claim 1, It is characterized in that The preparation method of the modified acrylate polyurethane is as follows: S1. Heat the polyether polyol to 110° C. and, while ensuring that the container is sealed, pump the negative pressure to 0.2 MPa and maintain for 1 hour; S2, the system temperature is lowered to 40-50°C, the catalyst I and the diisocyanate are slowly added dropwise, the temperature is heated to 50-70°C, and the temperature is maintained for reaction for 3-10 hours until the residual -NCO in the product reaches the theoretical -NCO, thereby obtaining a polyurethane intermediate I; S3, after adding the catalyst I dropwise into the polyurethane intermediate I, add the catechol series, control the temperature at 80-100°C, react for 2-10 hours, add the acrylate end-capping agent, continue the reaction until the residual -NCO of the product is less than 5‰, and then stop the reaction to obtain the modified acrylate polyurethane.

3. The 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties according to claim 2, It is characterized in that The polyether polyol includes polypropylene glycol (PPG) and polyethylene glycol (PEG), and the polyether polyol includes at least one of PPG200, PPG400, PPG600, PPG1000, PPG1500, PPG2000, PPG3000, PEG200, PEG300, PEG400, PEG600, PEG1000, PEG2000, and PEG4000; the diisocyanate includes toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, dicyclohexyl At least one of methane diisocyanate and hexamethylene diisocyanate; the catechol series includes at least one of 4-(2-ethylamino)benzene-1,2-diphenol, 4-(2-aminoethyl)-1,2-benzene hydrochloride, 3,4-dihydroxybenzylamine hydrobromide, 3,4-dihydroxynorephedrine, and [2-(3,4-dihydroxyphenyl)-2-hydroxy-ethyl]ammonium chloride; the acrylate end-capping agent includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and pentaerythritol triacrylate.

4. The 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties according to claim 1, It is characterized in that The preparation method of the modified acrylate epoxy resin is as follows: the epoxy resin and the polymerization inhibitor are mixed and heated to 60-120° C., after adding catalyst II, the acrylic acid is slowly added dropwise, and the reaction is heated to 100-160° C. The product epoxy ester is measured to be less than 1 mol / kg and the acid value is less than 2 mg KOH / g, thereby obtaining the modified acrylate epoxy resin.

5. The 3D printing dental resin having both long-lasting antibacterial and anti-drug resistance properties according to claim 4, It is characterized in that The epoxy resin is an o-cresol type novolac epoxy resin compound; the polymerization inhibitor includes at least one of 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tris(2-methylpropionyloxy)-1,3,5-triazine, p-hydroxyanisole, hydroquinone, and 2,5-dimethylhydroquinone; and the acrylic acid includes at least one of acrylic acid and methacrylic acid.

6. The 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties according to claim 1, It is characterized in that The preparation method of the nano silver particles is as follows: A1, dispersing the polyvinyl pyrrolidone into the ethylene glycol solution, mixing evenly at room temperature, then adding the silver nitrate thereto in a dark condition, stirring at room temperature for 30 to 60 minutes until all the solids are completely dissolved; A2, heating the A1 solution to 60-100°C, keeping the temperature for 12-18 hours, taking out the solution and centrifuging it, washing it with ethanol solution, and centrifuging it for more than 3 times; drying the solid product obtained by centrifugation in a forced air drying oven for 12 hours to obtain the nano silver particles.

7. The 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties according to claim 6, It is characterized in that The polyvinyl pyrrolidone includes at least one of polyvinyl pyrrolidone, polyvinyl pyrrolidone, and polyvinyl pyrrolidone.

8. The 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties according to claim 1, It is characterized in that The monomer diluent includes cyclotrimethylolpropane formal acrylate, o-phenylphenoxyethyl acrylate, o-phenylphenoxyethyl acrylate, 4-tert-butylcyclohexyl acrylate, benzyl acrylate, isodecyl acrylate, (ethoxy)phenol acrylate, tetrahydrocannabinol acrylate, ethoxyethoxyethyl acrylate, 1,6-hexanediol diacrylate, (ethoxylated) 1,6-hexanediol diacrylate, hydroxypivalic acid polyglycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, triethylene glycol diacrylate, (ethoxy)bisphenol A diacrylate, At least one of tricyclodecane dimethanol diacrylate, polyethylene glycol (400) diacrylate, polyethylene glycol (600) diacrylate, polypropylene glycol (400) diacrylate, trimethylolpropane triacrylate, 3 (ethoxy) trimethylolpropane triacrylate, 6 (ethoxy) trimethylolpropane triacrylate, (propoxy) propylene triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, 3 (propoxy) trimethylolpropane triacrylate, ethoxylated pentaerythritol tetraacrylate, (trimethylolpropane) tetraacrylate, and dipentaerythritol pentaacrylate.

9. The 3D printing dental resin with long-lasting antibacterial and anti-drug resistance properties according to claim 1, It is characterized in that The photoinitiator includes at least one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1-hydroxycyclohexylphenyl ketone, and 2-isopropylthioxanthone; and the auxiliary agent includes at least one of a leveling agent, a defoaming agent, or a wetting and dispersing agent.

10. The method for preparing the 3D printing dental resin having both long-lasting antibacterial and anti-drug resistance according to any one of claims 1 to 9, It is characterized in that The invention comprises the following preparation method: at room temperature, adding the modified acrylate polyurethane and the modified acrylate epoxy resin to the monomer diluent and mixing them evenly, then adding the auxiliary agent, the photoinitiator and the nano silver particles, and continuing to mix and stir for more than 30 minutes to obtain the 3D printing dental resin.